PENGENDALIAN PENYAKIT ANTRAKNOSA PADA TANAMAN CABAI MERAH MENGGUNAKAN AGEN HAYATI Trichodermaharzianum DAN Actinomycetes (The Control Anthracnose Disease on Red Pepper with Involve Agents Trichoderma harzianum and Actinomycetes) - L., Supriati; A. A, Djaya (Universitas Palangka Raya, 2016)
ABSTRACTThe research to study longevity and effectiveness involve agents Trichoderma harzianum andActinomycetes to control anthracnose disease on red pepper. The research using Divice CompleteRandom consist 2 phase, phase 1) Examination of materials ajuvan at liquid potato dextrose (LPD)media to longevity involve agents T. harzianum and Actinomycetes with 6 treatment is 1)Actinomycetes culture in 250 mL LPD, 2) Actinomycetes culture in 250 mL LPD+1% corn flour (b/v),3) Actinomycetes culture in 250 mL LPD+mollases 2% (v/v), 4) T. harzianum culture in 250 mLLPD, 5)T. harzianum culture in 250 mL LPD+1% corn flour (b/v), 6) T. harzianum culture in 250 mLLPD+mollases 2%, do at laboratory. Research of phase 2 to study involve agents T. harzianum andActinomycetes to control anthracnose disease on red pepper, treatment involve agents culture in LPD250 mL+1% corn flour media, consist 3 treatment that is: 1) no filtrat involve agents, 2) filtratActinomycetes 250 mL.L-1, 3) filtrat T. harzianum 250 mL.L-1, do at plastic house. Result of researchshow that addition of corn flour or mollases at LPD media improving population of T. harzianum until2 w.a.i (week after inoculation) but decline at 3-4 w.a.i, while addition of corn flour improvingpopulation of Actinomycetes compared to mollasses, improving till 3 w.a.i but decline at 4 w.a.i. Thecontrol use filtrat T. harzianum and Actinomycetes to anthracnose disease show is same effectivenesswith value effectiveness>69%.Keywords: Actinomycetes, Antracnose, T.harzianum.